SUBSTANTIATION OF APPLICATION OF ANTI-ICE CHEMICAL REAGENTS ON AUTOMOBILE ROADS WITH CEMENT CONCRETE COVERING - D. E. Yessentay,; A. K. Kiyalbaev,; S. N. Kiyalbay,; Borisyuk N.V, (Academic Scientific Journal of Chemistry, 2021)
In this paper, we consider the problem associated with the fight against slipperiness on roads with a hard type of road surface. It is known that on cement-concrete surfaces, the length of the braking distance is up to 10 times longer than on a snow roll formed on asphalt-concrete surfaces. This phenomenon is especially dangerous in winter, as a sharp increase in humidity (as a result of warming) significantly reduces the strength properties of cement concrete. Chloride de-icers are highly hygroscopic. Being in the pores of cement concrete, chemical solutions begin to absorb moisture from the atmosphere. In asphalt concrete, such phenomena are practically absent. Moisture, which is located in the pores of cement concrete, on its surface occurs "staining" and peeling. In the article, the authors pay special attention to the climatic conditions of Kazakhstan. The average air temperature of the coldest month on average in the Akmola region is 25-27oC, in the Eastern region-31-36oc, in the North– -26-29 OS, and in the South-3-10 OS. Annual precipitation amounts to 260-300, 340-370, 300-340 and about 150 mm, respectively. the duration of the cold period in the year varies between 6-7, 6-7, 5-6 and 3-4 months. It is climate factors that make it difficult to use chemical reagents as anti-icing materials on roads with a cement-concrete surface. This article discusses the theoretical basis for the destruction of the crystal structure of snow and ice formations from the influence of chemical reagents. They established a natural dependence of the freezing force of snow and ice formations on the impact of various types of salt solutions. Also, laboratory studies have established the effect of the concentration of salt solutions on the loss of strength of cement concrete over time